Shakespeare stories - Garfield, Leon.; Shakespeare, William, 1564-1616.; Foreman, Michael, 1938- (New York : Schocken Books, 1985)
An acclaimed author has rewritten twelve of Shakespeare's plays in narrative form, retaining much of the original language, and thus the flavor of the bard's dramas.
Twelfth night -- King Lear -- The tempest -- The merchant of Venice -- The taming of the shrew -- King Richard the Second -- King Henry IV, part one -- Hamlet -- Romeo and Juliet -- Othello -- A midsummer night's dream -- Macbeth.
Keywords: Shakespeare, William, -- 1564-1616 -- Stories, plots, etc. -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Adaptations -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Adaptations; Children's stories, English